Wave normal angles of whistler mode chorus rising and falling tones. Issue 12 (3rd December 2014) - Taubenschuss, Ulrich; Khotyaintsev, Yuri V.; Santolík, Ondrej; Vaivads, Andris; Cully, Christopher M.; Contel, Olivier Le; Angelopoulos, Vassilis
Abstract: We present a study of wave normal angles ( θ k ) of whistler mode chorus emission as observed by Time History of Events and Macroscale Interactions during Substorms (THEMIS) during the year 2008. The three inner THEMIS satellites THA, THD, and THE usually orbit Earth close to the dipole magnetic equator (±20°), covering a large range of L shells from the plasmasphere out to the magnetopause. Waveform measurements of electric and magnetic fields enable a detailed polarization analysis of chorus below 4 kHz. When displayed in a frequency‐ θ k histogram, four characteristic regions of occurrence are evident. They are separated by gaps at f / f c, e ≈0.5 ( f is the chorus frequency, f c, e is the local electron cyclotron frequency) and at θ k ∼40°. Below θ k ∼40°, the average value for θ k is predominantly field aligned, but slightly increasing with frequency toward half of f c, e ( θ k up to 20°). Above half of f c, e, the average θ k is again decreasing with frequency. Above θ k ∼40°, wave normal angles are usually close to the resonance cone angle. Furthermore, we present a detailed comparison of electric and magnetic fields of chorus rising and falling tones. Falling tones exhibit peaks in occurrence solely for θ k >40° and are propagating close to the resonance cone angle. Nevertheless, when comparing rising tones to falling tones at θ k >40°, the ratio of magnetic to electric field shows no significant differences. Thus, we conclude that falling tones are generated under similar conditions as rising tones, with common source regions close to the magnetic equatorial plane. Key Points: Chorus risers have quasi‐parallel WNA and WNA close to resonance cone Chorus fallers have WNA predominantly close to resonance cone Risers and fallers at high WNA have similar magnetic and electric amplitudes